Determination of Flocculant Concentration to Increase Quality of Dilute SAP in Sugar Mills - Junianti, Fitri; Amin, Idi; Salsabila, Sahira; Lestari, Rianti Indah (INTEK: Jurnal Penelitian, 2024)
The quality of the sugar produced at a sugar factory depends on the dilute sap from the refining station process stages. The quality of the diluted liquid is influenced by the amount of impurities present. The more impurities contained in the diluted sap, the lower the rate of the diluted fluid obtained. To separate the contaminants present, process aids are needed, and one of them is flocculant. The concentration of flocculant used must be precise to maximize the separation process of sugar and impurities. The determination of flocculant addition has traditionally been based on visual observations of the dilute sap obtained. The results of the research show that the addition of flocculant that has the most influence in improving the quality of diluted sap is a flocculant concentration of 3 ppm, which has a turbidity of 28.69 NTU, pH 7, pol 10.82%, brix 12.88%, and a purity value of 84.01%.